(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article explores the relevance, essence and practical significance of the synergy of strategic management and leadership in uncertain conditions. The approaches of leading scientists to the role of leadership in supporting strategic initiatives are summarized. It is shown that it is the integration of strategic management with adaptive, transformational and servant leadership that ensures the sustainability and innovativeness of enterprises. A model of synergy is proposed and five significant managerial conditions for its effective implementation are formulated.